NORA’S CHARACTER DEVELOPMENT AFTER APPARENT DEATH IN MATT HAIG’S THE MIDNIGHT LIBRARY - Juang Galuh Ratu Praditha; Ambar Andayani (Proceeding of Undergraduate Conference on Literature, Linguistic, and Cultural Studies, 2022)
This study aims to analyze the development of the main character, Nora, in Matt Haig’s the Midnight Library. The development of Nora’s character begins to look after she experiences the apparent death when she is between life and death. Apparent death is an experience where someone is transferred into another life. The writer uses a descriptive qualitative method and an intrinsic approach to analyze Nora’s character development which is influenced by the conditions and circumstances experienced by Nora. The data of this study is taken from the words and dialogues in Matt Haig’s the Midnight Library which shows the characters and character development of the main character, Nora. In analyzing the data, the writer uses the theory of character development by Perrine (2018). The analysis reveals that the apparent death has influenced the development of Nora’s character. At the beginning of the story, the writer finds out that Nora is a dispirited, petty-minded, pessimistic, ungrateful, and self- blameful person. After she experiences apparent death, she begins to realize the true meaning of her life. And then she becomes an open-minded, optimistic, grateful, and happier person after she experiences something big in her life which is when she is between life and death.